Adverse Selection in Mortgage Markets: Evidence from Ginnie Mae Early Buyouts - Bandyopadhyay, Arka P.; Kim, Dongshin; Smith, Patrick S. (Journal of Financial and Quantitative Analysis, 2026)
Abstract This article documents adverse selection in Ginnie Mae issuers’ early buyout decisions. Conditional on default, we find a 1 percentage point increase in interest rate spread increases the probability of an early buyout by 7–9 percentage points. Issuers buy out higher interest rate spread loans because they generate greater economic gains when they reperform. We illustrate how issuers acquire private soft information that provides direct insight into the likelihood of reperformance. Although the soft information is ostensibly collected on behalf of investors during the delinquent loan servicing process, issuers can exploit the information in their early buyout decisions.